A case of metastatic adenocarcinoma on a background of penoscrotal extramammary Paget's disease. (30th September 2015) - Christodoulidou, Michelle; Khetrapal, Pramit; Mitra, Anita; Muneer, Asif
Abstract : A 77-year-old man presented with a chronic lesion located in the left penoscrotal area. Apart from pruritus, bleeding and an occasional discharge from this area, he also reported reduced appetite and weight loss. Examination revealed an ulcerated skin lesion attached to a firm subcutaneous mass. Wide local excision of the lesion revealed invasive adenocarcinoma on a background of extramammary Paget's disease. Staging studies showed disseminated metastatic disease within the lymph nodes, and liver and bone metastases. He was treated with carboplatin and paclitaxel chemotherapy initially, but then continued only on Carboplatin chemotherapy due to side effects from Paclitaxel. Eleven weeks after the start of his chemotherapy, his restaging imaging showed reduced lymphadenopathy, unchanged liver metastasis and sclerosis of bone metastasis. With completion of chemotherapy, repeat imaging showed stable disease. The patient is currently on follow-up.